A hybrid method of entropy and SSAE-SVM based DDoS detection and mitigation mechanism in SDN. Issue 115 (April 2022) - Long, Zhang; Jinsong, Wang
Abstract: Software-defined networking (SDN) is a new network architecture that offers considerable management convenience and efficiency relative to conventional networks. However, the centralized control employed in SDN incurs a high risk of single point failure that is susceptible to distributed denial of service (DDoS) attacks. The present work addresses this issue by proposing a hybrid approach for detecting DDoS attacks using an initial detection module based on information entropy to quickly identify anomalous traffic and a second detection module based on machine learning with a stacked sparse autoencoder (SSAE)–support vector machine (SVM) architecture to confirm the suspected anomalous traffic. If DDoS traffic is detected, a defense module is implemented to restore normal network communication in a timely manner via an issued flow table. The effectiveness and efficiency of the proposed approach for DDoS detection is experimentally evaluated using both real-time and benchmark datasets in comparison with state-of-the-art methods. The results demonstrate that the proposed approach provides superior detection performance and identifies greater than 98% of existing DDoS traffic with greatly reduced training time and computational burden.